Minimal sizes of deletions detected by comparative genomic hybridization - Bentz, Martin; Plesch, Anja; Stilgenbauer, Stephan; Döhner, Hartmut; Lichter, Peter (Genes, chromosomes & cancer, 1998)
Comparative genomic hybridization (CGH) has been used widely for the molecular cytogenetic analysis of tumors. Until now, the spatial resolution of this technique for diagnosing deletions of chromosomal sequences has not been assessed in detail. In the present study, we performed CGH analyses on five DNA samples derived from B-cell leukemias with 11q deletions, the sizes of which ranged from 3 Mbp to 14-18 Mbp. CGH experiments were evaluated by two established commercial analysis systems. Deletions down to a size of 10-12 Mbp were diagnosed based on a diagnostic threshold value of 0.8, if the vast majority of cells carried the deletion. For cases with smaller deletions, the ratio profiles were shifted toward underrepresentation at the respective chromosomal bands; however, the diagnostic threshold value was not reached. In all five cases, there was complete agreement between the two image analysis systems. Genes Chromosomes Cancer 21:172-175, 1998. © 1998 Wiley-Liss, Inc.